1999
DOI: 10.1002/(sici)1099-1581(199903)10:3<195::aid-pat875>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and emission spectra of polyethylene terephthalate and polyethylene 2,6-naphthalate films

Abstract: With excitation by the light of the wavelengths longer than 320 nm, fluorescence spectra of polyethylene terephthalate (PET) films had somewhat different shapes from those excited below 300 nm through the intrinsic absorption of PET molecules. Also, in the measurements taken with a polarizer in front of the receiving monochoromator but none before the sample, the intensity ratio of parallel (to the draw axis of the film) and perpendicular components of the emission spectra was different if excited above 320 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The chosen solid support has advantages and disadvantages. While PET is the support used in many papers to study the behavior of similar copolymers (3,11,21), it has been reported to have fluorescent signals in the same spectral regions of thymine (22)(23)(24). Therefore, the spectral selectivity of this technique may not be enough, and the accurate characterization of the species involved in the curing process could not be achieved.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…The chosen solid support has advantages and disadvantages. While PET is the support used in many papers to study the behavior of similar copolymers (3,11,21), it has been reported to have fluorescent signals in the same spectral regions of thymine (22)(23)(24). Therefore, the spectral selectivity of this technique may not be enough, and the accurate characterization of the species involved in the curing process could not be achieved.…”
Section: Introductionsupporting
confidence: 81%
“…Comparing the spectra with data reported in refs. (22)(23)(24), as well as with the spectra obtained experimentally for PET and VPS (Figure 6(d)), a reasonable agreement was observed; in fact, the correlation between experimental and modeled spectra was evaluated in terms of similarity coefficients (26), obtaining values of 0.953 and 0.949 for PET emission and excitation spectra, and 0.998 and 0.979 for VPS emission and excitation spectra, respectively. Regarding the spectral features of the excitation and emission profiles assigned to VBT (blue line in Figure 6(c)), reported data for thymine fluorescence (20) indicate a comparable emission maximum at 400 nm (λ exc = 295 nm), even if no quantitative evaluation of such similarity is possible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence and excitation spectra of poly(ethylene terephthalate‐ co ‐2,6‐naphthalate) copolymers with less than 4 mol % DMN were studied; in this way, the energy transfer in the copolymers and their photodegradation were discussed 11. Comparing with that of PET, which emits two species of fluorescence, the fluorescence of PEN seems to be normal, forming a mirror image against the absorption spectra and following Kasha's law 12…”
Section: Introductionmentioning
confidence: 99%
“…The ability to detect these absorbances while collecting spectral data from tissues on top of PET can establish the depth of detection. Similarly, in the visible region, PET has a characteristic peak at 375 nm ( Ouchi et al, 1999 ). The depth of detection into the tissue was determined based on the minimum thickness of tissue from which the PET signal was not detected in the spectra, similar to that previously described in Padalkar and Pleshko, (2015 ).…”
Section: Methodsmentioning
confidence: 99%